"،The signs of inter nationalism in the view of Abooreyhne Birooni" - Behjatosadat Hejazi (تاریخ ادبیات)
Abooreyhane Birooni scholarly, mathematician, astrologer and aware to historic and social subjects, was borne in Biroon of kharazm in the mid of fourth century hejira. In spite of his engagement to politic jobs among ministration of kharazm shah and astrologer belong to sultan Mahmood, he hasn’t lost mentality of pry, brain and appealing himself as compared with truth and has appeared his congenital excogitate in create worthwhile compilations. The research of biography and moral exclusivities of prominent individuality gringo persons that have been lighten in the level of world; whilst is explanatory for cenogenesis, is very effective for most science discover and recognition of their value traces. Though in the extent of literary critic, some of the views emphasis on text, without author and his biography. Most important his quality are free thinker, without partiality and his inter nationalism views that have appeared in more his compilations particularly in the “Thahghighe Malelhend”. Doubtless, his system’s view had been touched of religious believes and Quran’s miracles too. Most basic question of author in this article is that, what signs are based his freethinker view and inter nationalism in the “Thahghighe Malelhenad”? This research is performed to style of analysis text’s containing.